Dietary Selenium in Immune Mechanisms During an Enteric Bacterial Infection (OR12-08-19). (13th June 2019) - Nettleford, Shaneice; Zhao, Luming; Fraser, James; Dey, Adwitia; Desai, Dhimant; Amin, Shantu; Carlson, Brad; Xiong, Na; Hankey, Pam; Paulson, Robert; Cantorna, Margherita; Prabhu, K Sandeep
Abstract: Objectives: Enteropathogenic Escherichia coli (EPEC) poses a great threat to developing countries, as EPEC can result in diarrhea and colitis in children. Interestingly, the effect of trace element nutritional deficiencies as well as their supplementation on disease pathogenesis is increasingly being recognized. We have previously reported that supplementation of mice with selenium (Se), a trace element that is incorporated into selenoproteins as the 21 st amino acid, resulted in the amelioration of chemically induced colitis through the downregulation of pro-inflammatory mediators of the arachidonic acid pathway, including prostaglandin E2 (PGE2). Here we examined the effects of Se supplementation on immune responses during an enteric infection with Citrobacter rodentium, a natural murine enteropathogen. Methods: C57BL/6 mice placed on Se-deficient (0.01 ppm Se), Se-adequate (0.08 ppm Se), or Se-supplemented (0.4 ppm Se) diets for 8 weeks were infected with Citrobacter rodentium, the murine equivalent of EPEC with a shared core set of virulence factors. Mice were euthanized, and colons were collected for further analysis including western blots and flow cytometry. Results: Se-deficient mice experienced increased bacterial burden, mortality, and decreased colon length following infection, compared to Se-adequate and Se-supplemented mice. Studies revealed that there was an increase type 3 innate-lymphoid cells (ILC3s) and IL-22 producing T helper 17 (Th17) cells, but a decrease in regulatory T- cells (Tregs) and 15-prostaglandin dehydrogenase (15-PGDH), the enzyme that preferentially oxidizes PGE2, in the colon of Se-deficient mice compared to Se-adequate and Se-supplemented mice. Treatment of Se-adequate mice with CAY10397, an inhibitor of 15-PGDH, increased the bacterial burden following infection. Infection of mice that lack expression of selenoproteins in macrophages ( Trsp fl/fl LysM Cre ) showed increased mortality despite being fed diets replete with Se. Conclusions: Adequate to supplemental levels of dietary Se is required to maximize the expression of selenoproteins to effectively mediate resolution of enteric infections. Selenoproteins act through diverse mechanisms, including modulation of immune responses and inflammation through the oxidative metabolism of PGE2 . Funding Sources: National Institute of Health.